Sleep quality and athletic performance according to chronotype - Lim, S.-T.; Kim, D.-Y.; Kwon, H.-T.; Lee, E. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background: When studying the quality of sleep in relation to athletic performance, the athlete`s chronotype and habitual time consider important factors. We aim to investigate the sleep quality and athletes` performance according to chronotype in elite athletes. Methods: Three hundred forty elite athletes (males = 261, females = 79) were recruited for the present study. All participants were screening for chronotype by the Korean versions of the Morningness - Eveningness Questionnaire (MEQ-K). The Pittsburgh Sleep Quality Index (PSQI) and Wingate Anaerobic Test (WAnT) were measurement after screening. Results: PSQI global score, PSQI sleep quality, PSQI sleep onset latency, PSQI sleep disturbance, and PSQI daytime dysfunction were significant differences among the groups. WAnT mean power (W), mean power (W/kg), peak power (W), and peak power (W/kg) were significant differences among the groups. A negative correlation coefficient was found between PSQI score and WAnT mean power (W) (r = - 0.256, p < 0.01), mean power (W/kg) (r = - 0.270, p < 0.01), peak power (W) (r = - 0.220, p < 0.01), and peak power (W/kg) (r = - 0.248, p < 0.01). Conclusions: This study indicates that related poor sleep quality and late-type chronotype may reduce the athletes` performance in elite athletes. In addition, the sleep quality is much higher in the early-type chronotype than in the late-type chronotype. Moreover, it also the athletic performance was better in the early-type chronotype than in the late-type chronotype.